2017
DOI: 10.3168/jds.2016-12229
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between early-life growth, intake, and birth season with first-lactation performance of Holstein dairy cows

Abstract: The objective was to determine the relationships between early-life parameters [including average daily gain (ADG), body weight (BW), milk replacer intake, starter intake, and birth season] and the first-lactation performance of Holstein cows. We collected data from birth years 2004 to 2012 for 2,880 Holstein animals. Calves were received from 3 commercial dairy farms and enrolled in 37 different calf research trials at the University of Minnesota Southern Research and Outreach Center from 3 to 195 d. Upon tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 16 publications
5
35
1
Order By: Relevance
“…16 In another study, researchers observed that for every 1 kg of average daily gain during the first six to eight weeks of life translated into an additional 544 kg of milk in first-lactation. 17 Unlike the other study, 15 calves in this data set were fed a conventional milk replacer (22%: 20%). 17 In conclusion, optimizing growth during the pre-weaning phase will likely increase future milk production.…”
Section: New Developments In Calf Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In another study, researchers observed that for every 1 kg of average daily gain during the first six to eight weeks of life translated into an additional 544 kg of milk in first-lactation. 17 Unlike the other study, 15 calves in this data set were fed a conventional milk replacer (22%: 20%). 17 In conclusion, optimizing growth during the pre-weaning phase will likely increase future milk production.…”
Section: New Developments In Calf Feedingmentioning
confidence: 99%
“…17 Unlike the other study, 15 calves in this data set were fed a conventional milk replacer (22%: 20%). 17 In conclusion, optimizing growth during the pre-weaning phase will likely increase future milk production.…”
Section: New Developments In Calf Feedingmentioning
confidence: 99%
“…In addition to maternal effects, seasonal effects on long-term offspring performance have been described. In dairy cattle, research on the effect of birth month shows conflicting results, not only between studies but also between herds (Soberon et al, 2012;Chester-Jones et al, 2017;Van Eetvelde et al, 2020a). However, a similar trend is seen as in human studies.…”
Section: Milk Yield and Longevitymentioning
confidence: 99%
“…The dairy industry has continually moved toward feeding more milk or milk replacer (MR) to young calves for benefits in improved growth rates (Diaz et al, 2001), health outcomes (Ballou et al, 2015), welfare (von Keyserlingk et al, 2009), and potential for improved milk production in the first and subsequent lactations (Gelsinger et al, 2016). However, some studies have illustrated that dry feed intake is equally influential on increasing early growth rates and later performance in lactation in replacement heifers (Gelsinger et al, 2016;Chester-Jones et al, 2017). When more milk or MR is fed to a calf, starter intake is less.…”
Section: Introductionmentioning
confidence: 99%